Application of inclined tube settlers in wastewater treatment - Prakarn Bunchueydee; Nguyen Cong Thanh; Yang, Yi Ping; Htun, Maung Nay; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1975)
This research covers the investigation of the primary and secondary clarifier performance. Primary Clarification AIT raw sewage was used as the raw wastewater which was discharged to 211W x 211D x 2'L PVC tube clarifier. The effects of angles (300-600), cross-sectional flow rate (5.75-12.65 m3/m2-hr), initial total solids concentration on the tube settler performance were investigated. Also the formulas developed by YAO (1970), HERNANDEZ, and WRIGHT (1970) were used for studying the effect of critical falling velocity and cross sectional flow velocity. The results show that the primary clarifier can be operated at the cross-sectional flow rate 5.75 m3/m2-hr. with 6.3 min. detention time. The effluent total solids concentration less than 100 mg/l, effluent settleable solids 2 ml/l can be achieved at any angle . In terms of total solids, tube settler of 60 degrees inclined angle gave the lowest level of performance. As the formulas were applied it was found that the performance of tube settler decreases down as the angle or critical falling velocity increases. Secondary Clarification 1000 mg/l COD of sucrose was used as the raw waste for two 2"W x 2"D x 2'L secondary in parallel clarifiers. The parameters investigated were effect s of sludge volume index, flow rate on the performance of secondary clarifier assembled at 60 degrees inclined angle which handle the effluent MLSS from the aeration tank (0.25mD x 0.25"W x l.25mL). The experiment was done at the cross-sectional flow rate 2.87-6.32 m3 /m2-hr. It is found that the results in terms of effluent quality is poor at various sludge volume index value. The sludge volume index does not affect the performance of tube settler at the cross-sectional flow rate 2.87-4.03 m3/m2-hr. It plays the important role when the cross-sectional flow rate increased to 5.18 m3/m2-hr. Its significance decreases down as the cross-sectional f low rate increased to 6.32 m3/m2-hr. It is unsuccessful to utilize the design parameter V2R proposed by HERNANDEZ and WRIGHT (1970). The possible way L of this failure is the fluctuation of initial MLSS concentration and also the significance of SVI which depends on the cross-sectional flow rate.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Sewer-pipe; Sewage disposal; Sewage -- Purification